2001
DOI: 10.1044/0161-1461(2001/008)
|View full text |Cite
|
Sign up to set email alerts
|

Social Behaviors of Children With Language Impairment on the Playground

Abstract: Specific intervention targeting social language skills in playground contexts may be warranted to include children with LI in social interactions at recess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 24 publications
6
114
0
6
Order By: Relevance
“…These findings support a large literature on younger children with impaired language showing that social outcomes are at risk in populations with communication impairment (Fujiki et al, 2001). The study also lends support to other studies which report that those with language impairments (but not autism) have subtle social cognition impairments (e.g., Farmer, 2000).…”
Section: Language Group and Social Outcomesupporting
confidence: 80%
See 2 more Smart Citations
“…These findings support a large literature on younger children with impaired language showing that social outcomes are at risk in populations with communication impairment (Fujiki et al, 2001). The study also lends support to other studies which report that those with language impairments (but not autism) have subtle social cognition impairments (e.g., Farmer, 2000).…”
Section: Language Group and Social Outcomesupporting
confidence: 80%
“…Some have suggested that language difficulties cause an impairment in social cognition (e.g., de Villiers & de Villiers, 2000) and there is some compelling intervention work to support this (Hale & Tager Flusberg, 2003). On the other hand, the wealth of research showing that those with SLI have social difficulties (e.g., Cantwell & Baker, 1978;Redmond & Rice, 1998;Conti-Ramsden & Botting, 2004;Fujiki et al, 2001), also opens the question as to whether these could arise from either inherent (co-morbid) social cognitive impairments or psychosocially as a result of poor language opportunities.…”
Section: Social Cognition In Relation To Social Skill and Language Inmentioning
confidence: 99%
See 1 more Smart Citation
“…An observational study of eight children with language impairments aged between 6 and 10 years found they displayed significantly more withdrawn behaviours than age-matched peers (Fujiki, Brinton, Isaacson, & Summers, 2001). In studies comparing teacher ratings of children with SLI and age-matched peers (5 to 13 years), children with SLI were judged to have significantly higher levels of reticence (motivated to interact but avoid and feel anxious in such interactions) and solitary-passive withdrawn behaviour, and these differences were large (Fujiki, Brinton, Morgan, & Hart, 1999;Fujiki, Spackman, Brinton, & Hall, 2004;Hart, Fujiki, Brinton, & Hart, 2004).…”
mentioning
confidence: 99%
“…In addition, studies have indicated that these children are more likely to show higher levels of withdrawn behavior as reported by teachers (Fujiki, Brinton, Morgan, and Hart, 1999;Redmond and Rice, 1998) and observed during free play settings (Fujiki, Brinton, Isaacson, and Summers, 2001). The factors responsible for children's reluctance to participate are both social and grammatical.…”
Section: Introductionmentioning
confidence: 99%